Myocardial perfusion quantification using the T1‐based FAIR‐ASL method: The influence of heart anatomy, cardiopulmonary blood flow and look–locker readout. Issue 5 (8th July 2013) - Kampf, Thomas; Helluy, Xavier; Gutjahr, Fabian T.; Winter, Patrick; Meyer, Cord B.; Jakob, Peter M.; Bauer, Wolfgang R.; Ziener, Christian H.
Abstract Purpose The quantification of myocardial perfusion using a Look–Locker flow‐sensitive alternating inversion recovery‐ arterial spin labeling experiment is considered. Due to the anatomy of the heart, a substantial but unintended partial inversion of the inflowing blood occurs during the slice‐selective inversion. Both, the partial inversion as well as the Look–Locker pulse train, influence the myocardial perfusion quantification and are addressed in this work. Methods The mean relaxation time approximation is used to calculate the monoexponential relaxation time of the signal in perfused tissue under Look–Locker readout. The left ventricular blood serves as an approximation of the inflowing blood in the description of FAIR‐ASL measurements with global and slice‐selective inversion to correctly quantify the myocardial perfusion. Results The analysis shows that the myocardial perfusion can be overestimated if the T1‐based quantification method is not adapted respecting the Look–Locker pulse train explicitly. Additionally, it turns out that without correction for the partial inversion of the blood pool during the slice‐selective inversion the myocardial perfusion is underestimated. Conclusion It is shown that the Look–Locker readout as well as the nonideal slice‐selective inversion experiment have a considerable influence and have to be included properly to correctly quantify myocardial perfusion. Magn Reson Med 71:1784–1797, 2014. © 2013 Wiley Periodicals, Inc.